Effects of Variety and Spacing on Percentage (%) Emergence and Grain Weight of Maize in Asaba Area of Delta State - E. C, Enujeke (Asian Journal of Agriculture and Rural Development, 2013)
This study was carried out in the Teaching and Research Farm of Delta State University, Asaba Campus from March 2008 to December 2009 to evaluate the response of maize varieties to three different plant spacings. It was a factorial experiment carried out in a Randomized Complete Block Design (RCBD) replicated three times. Ten maize varieties were evaluated under three different plant spacings for their percentage emergence and grain weight. The results of percentage emergence showed that open-pollinated variety BR9922-DMRSF2 which had 93.2% in 2008 and 93.8% in 2009 had highest percentage emergence. The results obtained from the grain weights indicated that hybrid variety 9022-13 that was sown at 75cm x 15cm which yielded 6.3 tha-1 in 2008 and 6.4 tha-1 in 2009 was superior, followed by open-pollinated variety BR9922-DMRSF2 which yielded 4.7tha-1 in 2008 and 4.9tha-1 in 2009. The effects of interaction showed that variety and space were significantly (p<0.05) different and positively affected maize grain weight. Based on the study, it is recommended that (i) Hybrid maize variety 9022-13 which was outstanding in grain weight be grown in the study area. Alternatively, farmers who prefer open-pollinated varieties could grow BR9922-DMRSF2. (ii) Spacing of 75cm x 15cm which resulted in better percentage emergence and highest grain weight be adopted in maize production.